Combined QTL and Genome Scan Analyses With the Help of 2b-RAD Identify Growth-Associated Genetic Markers in a New Fast-Growing Carp Strain - Su, Shengyan; Li, Hengde; Du, Fukuan; Zhang, Chengfeng; Li, Xinyuan; Jing, Xiaojun; Liu, Liyue; Li, Zhixun; Yang, Xingli; Xu, Pao; Yuan, Xinhua; Zhu, Jian; et al. (Frontiers in Genetics, 2018)
Common carp is one of the oldest and most popular cultured freshwater fish species both globally and in China. In a previous study, we used a carp strain with a long breeding tradition in China, named Huanghe, to create a new fast-growing strain by selection for fast growth for 6 years. The growth performance at eight months of age has been improved by 20.84%. To achieve this, we combined the best linear unbiased prediction with marker-assisted selection techniques. Recent progress in genome-wide association studies and genomic selection in livestock breeding inspired common carp breeders to consider genome-based breeding approaches. In this study, we developed a 2b-RAD sequence assay as a means of investigating the quantitative trait loci in common carp. A total of 4,953,017,786 clean reads were generated for 250 specimens (average reads/specimen = 19,812,071) with BsaXI Restriction Enzyme. From these, 56,663 SNPs were identified, covering 50 chromosomes and 3,377 scaffolds. Principal component analysis indicated that selection and control groups are relatively clearly distinct. Top 1% of Fst values was selected as the threshold signature of artificial selection. Among the 244 identified loci, genes associated with sex-related factors and nutritional metabolism (especially fat metabolism) were annotated. Eighteen QTL were associated with growth parameters. Body length at three months of age and body weight (both at 3 and 8 months) were controlled by polygenic effects, but body size (length, depth, width) at eight months of age was controlled mainly by several loci with major effects. Importantly, a single shared QTL (IGF2 gene) partially controlled the body length, depth, and width. By merging the above results, we concluded that mainly the genes related to neural pathways, sex and fatty acid metabolism contributed to the improved growth performance of the new Huanghe carp strain. These findings are one of the first investigations into the potential use of genomic selection in the breeding of common carp. Moreover, our results show that combining the Fst, QTLmapping and CRISPR–Cas9 methods can be an effective way to identify important novel candidate molecular markers in economic breeding programs.